Visual Experiences during Paralysis - Whitham, Emma M.; Fitzgibbon, Sean P.; Lewis, Trent W.; Pope, Kenneth J.; DeLosAngeles, Dylan; Clark, C. R.; Lillie, Peter; Hardy, Andrew; Gandevia, Simon C.; Willoughby, John O. (Frontiers in Human Neuroscience, 2011)
Rationale Paralysed human volunteers (n=6) participated in an electroencephalographic study after which they undertook studies of attempted eye movement. The interventions tested a central, intentional component to one’s internal visual model. Methods Six subjects reclined in a supported chair and were ventilated after paralysis (cisatracurium, 20 mg intravenously). In illumination, subjects were requested to focus alternately on the faces of investigators standing on the left and the right within peripheral vision. In darkness, subjects were instructed to look away from a point source of light. Subjects were to report their experiences after reversal of paralysis. Results During attempted eye movement in illumination, one subject had an illusion of environmental movement but four subjects perceived faces as clearly as if they were in central vision. In darkness, four subjects reported movement of the target light in the direction of attempted eye movements and three could control the movement of the light at will. Conclusion The hypothesis that internal visual models receive intended ocular-movement-information directly from oculomotor centres is strengthened by this evidence.